2015
DOI: 10.1093/jscr/rjv026
|View full text |Cite
|
Sign up to set email alerts
|

Floating patella associated with lymphoedema

Abstract: Ipsilateral injury of more than one component of the knee extensor apparatus is rare. It is mostly associated with previous trauma, surgery, immunosuppression therapy and systemic disease. We present the first documented case of a spontaneous bifocal disruption of the knee extensor apparatus (i.e. floating patella) associated with lymphoedema. This case highlights the importance of considering lymphoedema as another risk factor for rupture of the knee extensor apparatus. It also highlights the importance of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This case report presents a bifocal injury to the knee extensor apparatus where both the patella and quadriceps tendons were fully torn along with a superior pole avulsion fracture of the patella. Although multiple ruptures to the ipsilateral quadriceps and patellar tendons are rare, similar injuries have been documented previously 3,5-9 . Kang et al proposed a classification system for bifocal knee extensor apparatus injuries with 5 types: (1) rupture of the patellar tendon at the tibial tubercle with avulsion of the tibial tubercle, (2) rupture of the patellar tendon at the tibial tubercle with avulsion of the inferior pole of the patella, (3) rupture of the quadriceps tendon at the superior pole of the patella with avulsion of the tibial tubercle, (4) avulsion of the inferior pole of the patella with avulsion of the tibial tubercle, and (5) avulsion of the patella and quadriceps tendons directly from their patellar attachments.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This case report presents a bifocal injury to the knee extensor apparatus where both the patella and quadriceps tendons were fully torn along with a superior pole avulsion fracture of the patella. Although multiple ruptures to the ipsilateral quadriceps and patellar tendons are rare, similar injuries have been documented previously 3,5-9 . Kang et al proposed a classification system for bifocal knee extensor apparatus injuries with 5 types: (1) rupture of the patellar tendon at the tibial tubercle with avulsion of the tibial tubercle, (2) rupture of the patellar tendon at the tibial tubercle with avulsion of the inferior pole of the patella, (3) rupture of the quadriceps tendon at the superior pole of the patella with avulsion of the tibial tubercle, (4) avulsion of the inferior pole of the patella with avulsion of the tibial tubercle, and (5) avulsion of the patella and quadriceps tendons directly from their patellar attachments.…”
Section: Discussionsupporting
confidence: 72%
“…Song et al discussed a 35-year-old man with complete rupture of the quadriceps and patellar tendons after a motor vehicle accident 5 . In 2015, Vun et al reported a case of a 54-year-old man with lymphedema who experienced a near-complete rupture of the quadriceps tendon and a complete rupture of the patellar tendon after slipping on the stairs 6 . In 2019, Sam et al presented the case of a 33-year-old man with rupture of the quadriceps tendon, patellar tendon, and anterior cruciate ligament after an athletic injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations